Live Organoid Cyclic Imaging - David E. Reynolds; Yusha Sun; Xin Wang; Phoebe Vallapureddy; Jianhua Lim; Menghan Pan; Andres Fernandez Del Castillo; Jonathan C. T. Carlson; Mark A. Sellmyer; MacLean Nasrallah; Zev Binder; Donald M. O'Rourke; et al. (Advanced Science, 2024)
Abstract Organoids are becoming increasingly relevant in biology and medicine for their physiological complexity and accuracy in modeling human disease. To fully assess their biological profile while preserving their spatial information, spatiotemporal imaging tools are warranted. While previously developed imaging techniques, such as four‐dimensional (4D) live imaging and light‐sheet imaging have yielded important clinical insights, these technologies lack the combination of cyclic and multiplexed analysis. To address these challenges, bioorthogonal click chemistry is applied to display the first demonstration of multiplexed cyclic imaging of live and fixed patient‐derived glioblastoma tumor organoids. This technology exploits bioorthogonal click chemistry to quench fluorescent signals from the surface and intracellular of labeled cells across multiple cycles, allowing for more accurate and efficient molecular profiling of their complex phenotypes. Herein, the versatility of this technology is demonstrated for the screening of glioblastoma markers in patient‐derived human glioblastoma organoids while conserving their viability. It is anticipated that the findings and applications of this work can be broadly translated into investigating physiological developments in other organoid systems.